PENGEMBANGAN KREATIVITAS GURU DALAM PROSES PEMBELAJARAN - Ahmad Syaikhudin (LP2M Universitas Ibrahimy, 2013)
This research aimed to reveal teachers’ creativity in teaching the skills of writing in Indonesian at the higher grades of SD Ma’arif Ponorogo. The teachers’ creativity is teaching materials, implementing teaching methods, instructional media, and learning resources in the implementation of the teaching and learning of the skills.This research was qualitative and phenomenology in approach. The data were obtained from informants consisting of the headmaster, teachers, and students as well as from activities in the teaching-learning process and documents related to the learning of the skills of writing in Indonesian at the school. The data were collected by conducting interviews and observations and taking notes from documents.The research results could be concluded as follows. First, the teachers of Indonesian have been creative in presenting materials for the teaching of the writing skills by using imaginative concepts, stimulating original ideas and works, employing variation in the patterns of interaction, teaching style, and message variety, and applying immediate evaluation. Second, the teachers have been creative in implementing the teaching methods used by applying a brainstorming method and combining existing methods. Third, they have been creative in developing instructional media and learning resources by producing self-made media,. The media made by the teachers are in the form of story synopses, letters, announcements, written reports, and poems. The modified media and learning resources are based on the already existing ones.